Ceropsylla pouteriae Burckhardt sp. nov. (Hemiptera: Psylloidea: Triozidae), a new species of jumping plant-louse inducing galls on the leaves of Pouteria ramiflora (Mart.) Radlk. (Sapotaceae): taxonomy, gall structure and histochemistry. Issue 31 (26th August 2019) - Oliveira, Denis Coelho De; Burckhardt, Daniel; Calácio, Tácito De Freitas; Kuster, Vinícius Coelho; de Queiroz, Dalva Luiz
ABSTRACT: Ceropsylla pouteriae Burckhardt sp. nov. is described and illustrated from Brazil: Minas Gerais. It induces pit galls on the leaves of Pouteria ramiflora (Mart.) Radlk. (Sapotaceae), a characteristic tree of the Cerrado biome. The previously artificial genus Ceropsylla is redefined and six species are transferred from Ceropsylla to Trioza as Trioza angustirerta (Li, 2011), comb. nov., Trioza celticola (Li, 2011), comb. nov., Trioza cestolemba (Li, 2011), comb. nov., Trioza discrepans (Tuthill, 1945), comb. nov., Trioza martorelli (Caldwell, 1942), comb. nov. and Trioza pulchra (Tuthill, 1945), comb. nov. The psyllids on Sapotaceae are reviewed and the phylogenetic relationships of Ceropsylla briefly discussed. The Ceropsylla pouteriae gall develops from cellular hypertrophy and hyperplasia of the mesophyll leaf tissue, as well as neoformation of vascular tissues. The hypertrophy of the palisade parenchyma cells leads to the formation of the adaxial cortex of the gall. The abaxial cortex originates from the spongy parenchyma. The elongation of the adaxial and abaxial cortex is responsible for the intralaminar gall shape. The neoformation of vascular bundles is an important feature for the phloem feeding Ceropsylla pouteriae . The intralaminar morphotype of the C. pouteriae gall showed a simple anatomical structure. It lacks defence-related compounds and nutritive tissue. The structural simplicity contrasts with the presence of chemical substances in the gall tissue.